2018
DOI: 10.15587/1729-4061.2018.126427
|View full text |Cite
|
Sign up to set email alerts
|

Improving the reliability of information­control systems at power generation facilities based on the fractal­cluster theory

Abstract: Papers [6, 7] demonstrate contemporary requirements to technical means and mathematical software for ICS for STC in APCS in terms of life cycle, reliability, safety, and failure-free operation considering the number of control points for technological parameters. One of the main criteria to ensuring high reliability of ICS for STC in APCS is the criterion of realization of the set of assigned algorithms and programs to process information for reliability in a real-time mode. Thus, to improve the reliability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…where ( 1 5 )where l is the scale of the spatial dimensionality, n is the number of structural elements (pores) in a cluster, k com.por is the filling factor of the electrolyte for a pore space, equal to (16): where V geom is the geometrical body volume, m 3 , V el is the electrolyte volume, m 3 ; k por is the coefficient of soil porosity. The number N can be determined from formula (17):…”
Section: Improvement Of the Methods For Calculating The Resistivitymentioning
confidence: 99%
See 1 more Smart Citation
“…where ( 1 5 )where l is the scale of the spatial dimensionality, n is the number of structural elements (pores) in a cluster, k com.por is the filling factor of the electrolyte for a pore space, equal to (16): where V geom is the geometrical body volume, m 3 , V el is the electrolyte volume, m 3 ; k por is the coefficient of soil porosity. The number N can be determined from formula (17):…”
Section: Improvement Of the Methods For Calculating The Resistivitymentioning
confidence: 99%
“…Consequently, the calculation and determining of the electrophysical parameters (SRS) by employing existing PC [17] for ELG, is probabilistic in nature, or very close to it, which significantly affects the operational reliability of autonomous mobile electrical installations. In this regard, the problem has been set to construct new physical models of ELG process, which would consider both the geometrical and structural-phase characteristics of the system "soilelectrolyte" and the electrophysical parameters of a porous medium in various soils.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In works [19,20], it is shown that surfaces with damaging defects have a heterogeneous and porous structure, which has fractal properties of self-similarity and scalability and can be characterized by a quantitative value -fractal dimensionality. Therefore, in the cited work, to study the fractal structure of the material of the FE shell and calculate the real geometric parameters of FE, it is proposed to use the computing apparatus of fractal geometry.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…With the aim of grouping the expert evaluations and deter mining a single value, it is advisable to use the cluster analysis which determines "the most possible significant solution". Unlike many other statistical procedures, cluster analysis methods are largely used at the initial stage of the research when there are no a priori hypotheses about classes [14]. Giv en the absence of any laws for the distribution of expert evalu ations for generalization of the expert evaluations on the mu tual interactions of the concepts of a fuzzy cognitive map, it is incorrect to use the methods of statistical analysis of data [15].…”
mentioning
confidence: 99%
“…Further on, the kmeans method is used to determine the value of the center of the cluster with the largest number of variables. The aim of the algorithm is to divide n observations by k clusters so that each observation could belong to exactly one cluster located at the shortest distance from the very ob servation [16].…”
mentioning
confidence: 99%